Pelatihan Pengomposan Intensif Untuk 68 KK Di RT 33 RW 06 Betungan Bengkulu - Yuliansyah, Yuliansyah; Olivia , Dini; Anwar , Monica; Utami, Wahyu; Geri, Geri; Fikri, Naufal Aziz Al; Fadilla, Rohayu; Nur’aini, Hesti; Fariadi, Herri (Utami Publisher, 2025)
This intensive one-day composting training program engaged 68 households in RT 33 RW 06 Betungan through a focused demonstration session. Using the Takakura method adapted for urban settlements, the training covered waste segregation, composting techniques, and troubleshooting common issues. Post-training evaluation revealed 78% comprehension of core concepts, with 32 households (47%) initiating composting . The condensed format proved effective for knowledge transfer but highlighted the need for follow-up support to ensure long-term adoption in high-density neighborhoods.